An Evaluation of the Use of Performance Measures in Health Care - Damberg, Cheryl L. (Rand Health Q, 2012)
The National Quality Forum (NQF), a private, nonprofit membership organization committed to improving health care quality performance measurement and reporting, was awarded a contract with the U.S. Department of Health and Human Services (HHS) to establish a portfolio of quality and efficiency measures. The portfolio of measures would allow the federal government to examine how and whether health care spending is achieving the best results for patients and taxpayers. As part of the scope of work under the HHS contract, NQF was required to conduct an independent evaluation of the uses of NQF-endorsed measures for the purposes of accountability (e.g., public reporting, payment, accreditation, certification) and quality improvement. In September 2010, NQF entered into a contract with the RAND Corporation for RAND to serve as the independent evaluator. This article presents the results of the evaluation study. It describes how performance measures are being used by a wide array of organizations and the types of measures being used for different purposes, summarizes key barriers and facilitators to the use of measures, and identifies opportunities for easing the use of performance measures moving forward.